Emptiness and its futures: staying and leaving as tactics of life in Latvia - Dzenovska, D (Berghahn Journals, 2018)
In the past 25 years, rural Latvia has become notably emptier. This emptying is the result of post-Soviet deindustrialization and large-scale outmigration, enabled by EU accession and exacerbated by the 2008 financial crisis. It is accompanied by lack of political protest, leading many to conclude that migration hinders political mobilization. Such conclusions derive from viewing leaving and staying as actions in relation to the state. Instead, leaving and staying should be viewed in relation to transnational forms of power. The people leaving the deindustrialized Latvian countryside to work in the English countryside are seeking futures past, namely, futures of stable employment and incremental prosperity. Those who stay in the emptying Latvian countryside create the future as a little bit more of the present.